2017
DOI: 10.1242/jeb.159764
|View full text |Cite
|
Sign up to set email alerts
|

The tendinopathic Achilles tendon does not remain iso-volumetric upon repeated loading: insights from 3D ultrasound

Abstract: Mid-portion Achilles tendinopathy (MAT) alters the normal three-dimensional (3D) morphology of the Achilles tendon (AT) at rest and under a single tensile load. However, how MAT changes the 3D morphology of the AT during repeated loading remains unclear. This study compared the AT longitudinal, transverse and volume strains during repeated loading of the tendinopathic AT with those of the contralateral tendon in people with unilateral MAT. Ten adults with unilateral MAT performed 10 successive 25 s submaximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 52 publications
5
37
1
Order By: Relevance
“…These findings provide the first in vivo data that describe free tendon morphological characteristics across all tendon regions in both tendinopathic and contralateral tendons. Our finding that the free tendon with MAT has a larger CSA and AP diameter throughout the entire tendon length at rest supports earlier studies that have shown an increase in the thickness and area of the mean whole free AT (Docking & Cook, ; Nuri et al., ) and a single site of free AT mid‐portion (Docking et al., ; Grigg et al., ; Tsehaie et al., ) as a result of pathological alterations in tendon structure and composition in individuals with MAT. The widespread alteration in tendon morphology of the tendinopathic tendon (i.e.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These findings provide the first in vivo data that describe free tendon morphological characteristics across all tendon regions in both tendinopathic and contralateral tendons. Our finding that the free tendon with MAT has a larger CSA and AP diameter throughout the entire tendon length at rest supports earlier studies that have shown an increase in the thickness and area of the mean whole free AT (Docking & Cook, ; Nuri et al., ) and a single site of free AT mid‐portion (Docking et al., ; Grigg et al., ; Tsehaie et al., ) as a result of pathological alterations in tendon structure and composition in individuals with MAT. The widespread alteration in tendon morphology of the tendinopathic tendon (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…Ten patients with unilateral MAT were included in the present study. The inclusion criteria were as follows: male adults, 18–60 years of age with unilateral symptomatic MAT, minimal duration of symptoms of 3 months, and a Victorian Institute of Sports Assessment‐Achilles tendon (VISA‐A) of <80 points (Nuri et al., ). The definition of MAT was pain, discomfort, tenderness to palpation, and focal thickening of the AT evident in both longitudinal and transverse scans of two‐dimensional (2‐D) ultrasound (2‐DUS) in the tendon mid‐portion (2–7 cm proximal to the AT calcaneal insertion; Maffulli et al., ; Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations